Os aristotelismos da linguagem das variáveis em sociologia - Totaro, Paolo (Universidade do Vale do Rio do Sinos, 2006)
This dissertation is an epistemological critic of the language of variables, the quantitative approach in sociology founded by Paul Lazarsfeld. It hilights itself from the previous controversies directed against Lazarsfeld’s proposal because it isn’t developed from the historical interpretative point of view, but from an internal perspective to the logical itself of the mathematical empirical procedures. Its analytical fitting will be that one of the epistemological conditions pointed by Galileo Galilei’s work, which allowed, for the first time in the history of human thinking, the use of mathematics as descriptive language of the empirical phenomena. The lack of such conditions is individualized as the origin of all difficulty of the language of variables as well as of the whole validity of the argumentations directed against it
Keywords: análise das variáveis; ciência galileiana; epistemologia; Lazarsfeld, Paul; galilean science; epistemology; variables analysis; Ciências Humanas